The Effect of Pet Therapy and Artist Interactions on Quality of Life in Brain Tumor Patients: A Cross-Section of Art and Medicine in Dialog - Stefan Petranek; Jennifer Pencek; Mahua Dey (Behavioral Sciences, 2018)
With the evolution of modern medical treatment strategies, there also comes the realization that many times we reach a point where traditional goals of medical care, such as overall survival or disease-free survival, are not realistic goals for many patients facing devastating illnesses. One such disease is malignant primary brain tumors, known as malignant glioma (MG). With median survival of only 20.9 months following best available standard of care treatment strategies, including surgery, chemotherapy, radiation, and tumor treating fields, MG is one of the deadliest malignancies of the modern era. Along the course of treating patients with MG, clinicians often realize that traditional treatment therapies can at best provide incremental benefit of symptom management without any survival benefit. However, even in these difficult situations, it is possible to make significant positive changes in patients’ health-related quality of life (HRQoL) using creative, non-traditional interventions. In this paper, we describe the initial findings from our project that takes a unique approach to studying the intersections of clinical care and art by using pet therapy and art-making as interventions for patients diagnosed with brain tumors. Our preliminary findings suggest that pet therapy and the ability to reflect as well as speak about their journey through a life-altering disease significantly increases patients’ overall feeling of wellbeing and reduces anxiety about future uncertainty.